A Systematic Review of Qualitative Studies on Critical Thinking in EFL Speaking Instruction - Andi Rahmayanti; Iskandar Sulaiman; Amirullah Abduh (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Critical thinking is increasingly seen as an important competency in learning to speak English as a Foreign Language (EFL), but qualitative evidence regarding its implementation and development is still scattered and has not been comprehensively synthesized. This research aims to synthesize the results of qualitative research regarding the conceptualization, implementation, and experiences of students and teachers in developing critical thinking through EFL speaking learning. The research was conducted using a systematic literature review method following PRISMA guidelines. Data sources are reputable scientific articles published in the 2019–2024 period and obtained from various academic databases. Articles were selected based on predetermined inclusion and exclusion criteria, then analyzed using thematic synthesis techniques. The results of the study show three main themes, namely: (1) critical thinking is understood as the ability to analyze, evaluate, provide reasons and make decisions in speaking activities; (2) learning strategies such as discussion, debate, problem-based learning, argumentation, and Content and Language Integrated Learning (CLIL) are effective in encouraging the development of critical thinking; and (3) teachers and students view speaking activities as a potential means for developing critical thinking skills. This study also identified research limitations in aspects of assessment, longitudinal studies, and EFL contexts that are still underrepresented. Research findings emphasize the importance of implementing dialogical and reflective speaking learning to develop critical thinking skills optimally.